Assessing Health Risk For Community Adaptation In Urban Heat Island Area Of Padang City - Putri Nilam Sari (Fakultas Kesehatan Masyarakat Universitas Andalas, 2020)
Areas classified as Urban Heat Islands (UHI) have a higher health risk due to climate change. High population activity, increasing population density, and low vegetation cover cause this area to become warmer than its surroundings. From the detection of the spatial pattern, Padang City has nine sub-districts belonging to UHI. In this area, environmental problems often occur due to climate calamities and have an impact on health. Therefore, this study was to determine the classification of public health risks and community adaptation to climate change in urban heat island areas. This research was conducted on 141 households in Koto Tangah sub-district as the large UHI area and highly prone to climate problems. Data collected by questionnaires, observation, and literature study. The risk assessment matrix was used to identify health risk status. The results showed that water pollution, respiratory problems, and diarrheal diseases are classified as high risks. The community needs to adapt to climate change, mainly doing routine physical activities, to increase immunity from many diseases.